Branched‐chain amino acid to tyrosine ratio is an essential pre‐treatment factor for maintaining sufficient treatment intensity of lenvatinib in patients with hepatocellular carcinoma. (4th October 2020) - Eso, Yuji; Nakano, Shigeharu; Mishima, Masako; Arasawa, Soichi; Iguchi, Eriko; Takeda, Haruhiko; Takai, Atsushi; Takahashi, Ken; Seno, Hiroshi
Abstract: Background/Purpose: Lenvatinib was recently approved as a novel agent for hepatocellular carcinoma. To maximize the therapeutic effect of anticancer drugs, it is essential to maintain treatment intensity by avoiding dose reduction or discontinuation. We aimed to identify essential factors contributing to achieve sufficient treatment intensity of lenvatinib. Methods: Seventy‐one patients who received treatment with lenvatinib were included in this study. We used the delivered dose intensity/body surface area ratio (DBR) to measure treatment intensity of lenvatinib. Results: 2M‐DBR (DBR for the first 60 days) of lenvatinib (≥206.7) was strongly correlated with objective response and was the significant factor contributing to prolonged progression‐free survival (PFS). Patients with high 2M‐DBR had significantly prolonged PFS compared with those who had low 2M‐DBR ( P < .001). Multivariate analysis revealed that pre‐treatment α‐fetoprotein and branched‐chain amino acid to tyrosine ratio (BTR) were significant factors in maintaining high 2M‐DBR of lenvatinib. Furthermore, patients with high pre‐treatment BTR (≥4.50) showed significantly longer PFS than those with low BTR ( P = .032). Conclusions: Maintaining high 2M‐DBR of lenvatinib is essential to increase response rate and PFS. To achieve high 2M‐DBR levels, preservation of pre‐treatment BTR is essential, suggesting the importance of nutritional management in the treatment for hepatocellular carcinoma with lenvatinib. Abstract : Maintaining the treatment intensity of lenvatinib contributes to improved response rates and prolonged progression‐free survival in hepatocellular carcinoma treatment. Eso and colleagues conclude that the pre‐treatment branched‐chain amino acid to tyrosine ratio is an essential factor for maintaining high dose intensity/body surface area ratio levels, suggesting that nutritional management is important.